Chemical characterization of archaeological pottery of the Lower Paraná River - Loponte, Daniel Marcelo (2019)
This paper analyzed the chemical composition of archaeological pottery produced by hunter-gatherers and horticulturist populations of the late Holocene of the lower Paraná basin. An energy dispersive X-ray fluorescence spectrometer was used to analyze the chemical composition of the sherds. The results obtained indicated that the analyzed samples, within certain parameters, showed some variability. The differences were even more significant when comparing the chemical composition of the pottery of the huntergatherer groups and that of the horticulturists. The main components identified in the archaeological pottery were grouped primarily with the location of production, that is, they were the result of local manufacturing. Within the trace-elements, the greatest variations in composition were observed in the strontium, which was assumed to vary in concentration levels throughout the region.